Feline Demodicosis by Demodex cati - Valandro, Marilia Avila; Pascon, João Paulo da Exaltação; Mistieri, Maria Lígia de Arruda; Gallina, Tiago (Acta Scientiae Veterinariae, 2016)
Background: Feline demodicosis is considered an uncommon dermatopathy in cats that is mainly caused by the mite Demodex cati, but in few cases D. gatoi may be involved. Although the clinical aspects and pathogeny of feline demodicosis are not completely understood, its clinical expression is believed to be associated with the presence of primary immunosuppressive agents. Thus, the aim of this study is to report the diagnosis and treatment of an infested cat by D. cati, associated with mixed intestinal parasitic infection. Case: An approximately 1-year-old male short hair cat which was grown in a rural area was presented at the Veterinary Hospital of the Federal University of Pampa (Unipampa) in Uruguaiana, Rio Grande do Sul. The cat had alopecia, itching, excoriations on neck and head, and softened feces as clinical signs. Performed skin scrapings revealed eggs, larvae and adult forms of D. cati. In order to fnd possible immunosuppressive agents, exams for detection of feline immunodefciency virus (FIV) and feline leukemia virus (FeLV) were also performed. They revealed, however, negative results for FIV and FeLV infections. Moreover, coproparasitologic analysis revealed the presence of the intestinal parasites Trichuris sp., Ancylostoma sp., and Spirometra mansonoides. Thus, it was decided to proceed the treatment utilizing 0.2 mg/kg of moxidectin subcutaneously every four days and weekly shower with antiseptic shampoo containing 0.15% triclosan. In addition, it was prescribed oral doses of febendazol (50 mg/kg/day) for four days. After 20 days of treatment, the skin lesions had decreased signifcantly and the skin scrapings were negative for D. cati. In this way, the showers with 0.15% triclosan was suspended. Nevertheless, the treatment with moxidectin was maintained for more fours weeks until totalclinical healing was achieved with hair growth and absence of skin lesions. Furthermore, after the treatment with febendazol the animal feces had reached a normal consistency and new coproparasitologic analysis revealed negative results for the presence of intestinal parasites. Discussion: The diagnosis of Demodex cati was based on clinical history, physical examination (alopecia, excoriation in the head and neck) and microscopic visualization of the mite in skin scrapings. The treatment used with moxidectin, acaricidal quite safe and effective, widely used in treatment of canine demodicosis, but no reports about the use in cats. The mite D. cati is considered normal resident of cat’s skin, and the pathogenesis of demodicosis is still unknown. It is known that the playback exacerbated mite can present with skin lesions is commonly associated with immunosuppression states. The presence of three different intestinal parasites (Spirometra mansonoides, Trichuris sp., and Ancylostoma sp.) might have been essential for an immunosuppressive status of the cat and clinical development of demodicosis. Thus, this report supports the hypothesis that a primary immunosuppressive agent is necessary for clinical development of feline demodicosis. Nevertheless, further researches are necessary in order to determine the prevalence of feline demodicosis and correlate the presence of cestodes and development of this disease. In addition, this report highlights the therapeutic success utilizing na association of moxidectin and topic treatment with the treatment of possible immunosuppressive agents. Keywords: dermatopathy, imunossuppression, cat, therapy